MODEL-MODEL PENGEMBANGAN MEDIA DAN TEKNOLOGI PEMBELAJARAN BAHASA INGGRIS - M. Sabiqul Huda (ADIBA : JOURNAL OF EDUCATION, 2022)
This study aims to answer questions related to the concept of the development model. In addition, this article also focuses on discussing development models and learning technologies for English. The qualitative approach used and the method applied in this article is library research. Data collection is taken from various libraries, then reviewed and set aside. The results of this analysis design that the development model is a conceptual process of a model with the aim of refinement and enhancement of a previous model that has been previously done. Several models of media development and learning technology have their respective stages and processes in learning design. The ASSURE model consists of stages, Analyzing Students, Country Standards and Objectives, Choosing Strategies, Technology, Media, and Materials, Utilizing Technology, Media, and Materials, Requiring Student Participation, Evaluating and Revising. Then the ADDIE Model is in stages namely Analysis, Design, Development, Implementation, and Evaluation. Next, Dick and Carey consisted of Identify Instructional Goals, Conduct Instructional Analysis, Identify Entry Behaviors, Write Performance Objectives, Develop Criterion Tests, Develop Instruction Strategy, Develop and Select Instructional Materials, Develop and Conduct Formative Evaluation, Develop and Conduct Summative Evaluation.